The effect of exercise bike in 4 weeks on muscle performance among obese adults - Abd Azis, Muhammad Aiman Hakim; Abidin, Muhammad Amrun Haziq; Adnan, Aizzat; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Md Yusof, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the impact of a 4-week stationary cycling intervention on muscle endurance, balance, and strength among obese individuals, addressing the physical limitations often associated with being overweight. While cycling is recognized as a safe, low-impact exercise for this population, its short-term efficacy in enhancing muscle performance remains under-researched. By comparing pre- and post-test scores between experimental and control groups, the research seeks to determine if a brief cycling program can effectively mitigate functional declines and improve physical capabilities in individuals with obesity.